On the efficiency of competitive markets for input quotas: The case of emission permit trading - Efticios Sophocles Sartzetakis (Fondazione Eni Enrico Mattei (FEEM), 1999)
It is typical for economists and policy makers alike to presume that competitive markets allocate input licenses efficiently. This paper demonstrates that competition in the licenses market cannot assure efficiency when the product market is oligopolistic. We develop a model to provide the conditions under which a bureaucratic mechanism is welfare superior to a marketable input licenses system. Price taking behaviour in the licenses market ensures transfer of licenses to the less efficient firm which becomes more aggressive in the product market. A higher than the welfare maximising number of licenses are traded. When the input and final output technologies are positively correlated, competitive license trading may result in lower output and welfare.
Keywords: 330; Competitive trading of input quotas; oligopolistic product markets; economic efficiency; Umweltbelastung; Lizenz; Oligopol; Allokationseffizienz; Theorie